2015
DOI: 10.1002/anie.201507902
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐Free Reduction of Nonprecious Transition‐Metal Compounds: Generation of Amorphous Ni Nanoparticles for Catalytic C–C Bond Formation

Abstract: A salt-free procedure for the generation of a wide variety of metal(0) particles, including Fe, Co, Ni, and Cu, was achieved using 2,3,5,6-tetramethyl-1,4-bis(trimethylsilyl)-1,4-diaza-2,5-cyclohexadiene (1), which reduced the corresponding metal precursors under mild conditions. Notably, Ni particles formed in situ from the treatment of Ni(acac)2 (acac = acetylacetonate) with 1 in toluene exhibited significant catalytic activity for reductive C-C bond-forming reactions of aryl halides in the presence of exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 62 publications
(34 reference statements)
0
41
0
Order By: Relevance
“…We then found that the use of N , N ′‐bis(trimethylsilyl)‐1,4‐dihydropyrazine 5 as a reductant for 1 M cleanly and selectively furnished N , N ′‐dihydrodiazaporphyrins 3 M (Scheme ). N , N ′‐Disilyl‐1,4‐dihydropyrazine 5 serves as a versatile and strong reducing reagent for group 4–6 metal and late transition metal chlorides ,. When we carried out the reaction of 1 Ni with 1.6 equivalents of 5 in THF at room temperature, complete conversion of 1 Ni was confirmed by 1 H NMR spectroscopy.…”
Section: Figurementioning
confidence: 92%
“…We then found that the use of N , N ′‐bis(trimethylsilyl)‐1,4‐dihydropyrazine 5 as a reductant for 1 M cleanly and selectively furnished N , N ′‐dihydrodiazaporphyrins 3 M (Scheme ). N , N ′‐Disilyl‐1,4‐dihydropyrazine 5 serves as a versatile and strong reducing reagent for group 4–6 metal and late transition metal chlorides ,. When we carried out the reaction of 1 Ni with 1.6 equivalents of 5 in THF at room temperature, complete conversion of 1 Ni was confirmed by 1 H NMR spectroscopy.…”
Section: Figurementioning
confidence: 92%
“…7 displays poor solubility in common organics olvents andi sonly sparingly soluble in THF,w hich prevented the separation of this compound from MgCl 2 .T herefore, 1,4-bis(trimethylsilyl)-1,4-dihydropyrazine (8)w as employed as as alt-free reductant that has been previously used for the generation of low-valent transition metal and main-group element compounds. [87][88][89] Thus, treatment of 4 with one equivalent of 8 in toluene gave 7 in 64 %y ield as ap ink solid, by simple filtration of the reaction mixturea nd washing with toluene and hexane. Diphosphene 5 and diarsene 6 were also prepared by this route in high purity, albeit in lower yields (5:4 2%, 6:5 0%), whichc an be ascribed to their higher solubility in hydrocarbon solvents.…”
Section: Preparation and Characterizationmentioning
confidence: 99%
“…While it was originally envisioned that elimination of (Me 3 Si) 2 O from MO n by 1 might be a useful approach to MO n −1 , a recent application to support‐bound WO 3 gave instead tetravalent tungsten silyl esters, which is still a valuable 2 electron reduction, but without full elimination of W/O bonds and creation of lower metal coordination number . The method has also been applied to nanoparticle formation, silylation of B−F bonds and of α‐halo carbonyls, and deoxygenation of nitro compounds . In summary, the strengths and limitations of this attractive reagent are only just emerging …”
Section: Introductionmentioning
confidence: 99%